High speed growth of MAPbBr3 single crystals via low-temperature inverting solubility: enhancement of mobility and trap density for photodetector applications. Issue 17 (23rd April 2021) - Cho, Yunae; Jung, Hye Ri; Kim, Yeon Soo; Kim, Yejin; Park, Joohee; Yoon, Seokhyun; Lee, Yousil; Cheon, Miyeon; Jeong, Se-young; Jo, William
Abstract : High-quality CH3 NH3 PbBr3 hybrid perovskite single crystal growth and outstanding optoelectronic application using the complete dissolution at low temperatures based on low temperature solubility, which has been demonstrated for the first time. Abstract : There has been growing interest in organic–inorganic hybrid perovskites as a promising candidate for optoelectronic applications due to their superior physical properties. Despite this, most of the reported perovskite devices based on polycrystalline thin films suffer immensely from poor stability and high trap density owing to grain boundaries limiting their performance. Perovskite single crystal structures have been recently explored to construct stable devices and reduce the trap density compared to their thin-film counterparts. We present a novel method of growing sizable CH3 NH3 PbBr3 single crystals based on the high solubility characteristic of hybrid perovskites at low temperatures within inverse temperature crystallization. We compared both the crystallinity of perovskite single crystal structures and optoelectronic charge transport of single crystal photodetectors as a function of dissolution temperature. The performance of the photodetector fabricated with our large-scaled single crystal with high quality demonstrated low trap density, high mobility, and high photoresponse.